Aeschynomene - Joao Vendramini; Maria L. A. Silveira (EDIS)
This 3-page fact sheet is a minor revision that discusses Aeschynomene, a warm-season annual legume adapted to moist sites throughout the state, but mainly grown in South Florida. Seed of two species are commercially available to producers: Aeschynomene americana, also known as common aeschynomene, joint vetch or deer vetch, and Aeschynomene evenia, which has no common name. Written by J. Vendramini and M. L. A. Silveira, and published by the Agronomy Department, October 2016.